Mechanical damage in potato - Singh, Sukhwinder; Kumar, Dinesh; Singh, Birpal; Goyal, Suneel Kumar (Indian Farming, 2015)
Mechanical damage of potatoes is a huge loss to the country. Most efficient way to minimize this loss is to take utmost care at the time of pre and post harvest operations. Besides this, all involved in potato growing, trading, processing, packaging, transportation and storage need to be educated about availability of improved machines and equipment, their right operation and other practices by following which mechanical damage can be reduced significantly.